2021
DOI: 10.9734/arjom/2021/v17i1230346
|View full text |Cite
|
Sign up to set email alerts
|

Variable Viscosity and Chemical Reaction Effects on MHD Flow of Radiative Fluid Past a Stretching Sheet in the Presence of Joule Heating

Abstract: The focus of the present study is to examine chemical reaction and Joule heating effects on steady flow of a viscous radiating fluid in a porous medium under the influence of variable viscosity. The fluid viscosity is assumed to vary exponentially with temperature. The governing equations of ow, heat and mass transfer are transformed into ordinary differential equations using appropriate similarity transformations. The converted ordinary differential equations are then solved numerically by using fourth order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Studies on numerical analysis of heat generation effects on free convective radiative Newtonian fluid flow with chemical reaction was explored by Fagbade and Omowaye [5]. Samuel and Fayemi [6] presented the role of thermal radiation and chemical reaction in viscous dissipative incompressible flow of Newtonian fluid past a stretching sheet. Zeeshan et al [7] investigated the impacts of convective heat transfer and thermal radiation on Couette-Poiseuille flow with mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on numerical analysis of heat generation effects on free convective radiative Newtonian fluid flow with chemical reaction was explored by Fagbade and Omowaye [5]. Samuel and Fayemi [6] presented the role of thermal radiation and chemical reaction in viscous dissipative incompressible flow of Newtonian fluid past a stretching sheet. Zeeshan et al [7] investigated the impacts of convective heat transfer and thermal radiation on Couette-Poiseuille flow with mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al 23 investigated MHD free convection flow of an incompressible fluid taking into consideration radiation effects. Samuel and Fayemi 24 addressed convective boundary surface effects on laminar flow of optically thick radiating fluid. Pandey and Kumar 25 studied the radiation impact on incompressible nanofluid flow with viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar & Srinivas (6) have discussed the magneto-hydrodynamic nanofluid flow over a shrinking surface and they have observed that the higher the velocity of the fluid with the lower local Grashof number. Samuel (7) investigated the impact of hydromagnetic on Ohmic heating and viscous fluid on a porous sheet. Jagadeeshwar and Srinivasacharya (8) have numerically examined the heat transit of the Joule heating with convective boundary conditions on MHD fluid flow and they observed that the lower in Nusselt number as well as the higher in Biot number.…”
Section: Introductionmentioning
confidence: 99%